CREATIVE ACCOUNTING: TINJAUAN LITERATUR ATAS INOVASI DAN INTEGRITAS PELAPORAN KEUANGAN - Riyan Harbi Valdiansyah; Dian Widiyati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This study aims to provide a comprehensive literature review on creative accounting practices that are at the intersection of innovation and quality in financial statements. Some creative measures are used to make reports more attractive to investors. More often, however, they can also lead to highly unethical data manipulation. The purpose of this study is to provide a thorough review of creative accounting practices. In a Systematic Literature Review-based study will be analyzed from leading articles during the period 2020 - 2024, Researchers used specific search terms to find relevant publications (“Creative accounting”) The results showed that creative accounting can provide flexibility, but if used inappropriately, it can have serious consequences. Not only does this risk a loss of credibility, but there are also legal risks and sanctions. This research is highly dependent on the literature reviewed due to the lack of empirical data from various regional contexts. However, the findings suggest that regulation, supervision, and professional ethics are important to limit creative accounting, and this research will provide suggestions that academics, practitioners, and policy makers are to study in the future.